2021
DOI: 10.1002/cncr.33933
|View full text |Cite
|
Sign up to set email alerts
|

The cure of leukemia through the optimist's prism

Abstract: Progress is occurring at a dizzying rate across all leukemias. Since the authors' review of the topic in Cancer in 2018, numerous discoveries have been made that have improved the therapy and outcomes of several leukemia subsets. Hairy cell leukemia is potentially curable with a single course of cladribine followed by rituximab (10‐year survival, ≥90%). Acute promyelocytic leukemia is curable at a rate of 80% to 90% with a nonchemotherapy regimen of all‐trans retinoic acid and arsenic trioxide. The cure rate f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 183 publications
0
9
0
Order By: Relevance
“…The result showed that there was no significant difference in overall survival between the RCN1 high expression group and the RCN1 low expression group. We speculate that this may be related to the fact that the RCN1 high expression group is mainly associated with M3 types and FLT3 mutations, with M3 and FLT3 mutations having a good overall treatment outcome [71,72], leading to an improved survival rate in the high RCN1 group. Despite the relative success of treatment for M3 and FLT3 mutations, relapse remains a major obstacle [73,74].…”
Section: Discussionmentioning
confidence: 99%
“…The result showed that there was no significant difference in overall survival between the RCN1 high expression group and the RCN1 low expression group. We speculate that this may be related to the fact that the RCN1 high expression group is mainly associated with M3 types and FLT3 mutations, with M3 and FLT3 mutations having a good overall treatment outcome [71,72], leading to an improved survival rate in the high RCN1 group. Despite the relative success of treatment for M3 and FLT3 mutations, relapse remains a major obstacle [73,74].…”
Section: Discussionmentioning
confidence: 99%
“…Blinatumomab was approved by the FDA for MRD-positive acute lymphoblastic leukemia (ALL) after chemotherapy. Furthermore, chemotherapy-free regimens combining blinatumomab and tyrosine kinase inhibitors are becoming a frontline option for Philadelphia chromosome–positive ALL [ 61 ]. On the other hand, the combination of inotuzumab ozogamicin (InO), an ADC that covalently conjugates calicheamicin to a humanized anti-CD22 antibody, and salvage chemotherapy (mini-hyper-fractionated cyclophosphamide, vincristine, and dexamethasone [mini-hyper-CVD]) with or without blinatumomab was superior to InO or the chemotherapy alone in relapsed or refractory ALL [ 62 ].…”
Section: Bites Bikes Checkpoint Inhibitory T-cell–engaging Antibodies...mentioning
confidence: 99%
“…APL was reported as a rapidly fatal disease until the late 1980s [ 7 ]. Currently, it is considered the most curable subtype of AML with survival rates of 80% to 90%, with the combination of the all-trans-RA and arsenic trioxide (non-chemotherapy regimen) [ 8 , 9 ]. Eventually, the combination of these compounds and chemotherapy was also considered in the treatment of APL [ 7 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%